2020
DOI: 10.3390/ijms21041430
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-Disrupting Chemicals in Human Fetal Growth

Abstract: Fetal growth is regulated by a complex interaction of maternal, placental, and fetal factors. The effects and outcomes that chemicals, widely distributed in the environment, may have on the health status of both the mother and the fetus are not yet well defined. Mainly mixtures of chemical substances are found in the mothers and placenta. Exposure to endocrine-disrupting chemicals (EDCs) can be associated with fetal growth retardation, thyroid dysfunction, and neurological disorders. EDCs mostly interfere with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(51 citation statements)
references
References 80 publications
2
48
0
1
Order By: Relevance
“…EDCs can affect both fetal growth and subsequent action over the years, and some EDCs also act on the prenatal period [48].…”
Section: Obesogenic Hypotesismentioning
confidence: 99%
“…EDCs can affect both fetal growth and subsequent action over the years, and some EDCs also act on the prenatal period [48].…”
Section: Obesogenic Hypotesismentioning
confidence: 99%
“…Whether the impact from periodontal infection influences or explicates a direct effect is uncertain but suggests a potentially damaging interaction between periodontitis and preterm delivery (PTD) [23]. From the empirical findings, a clear interest focused on the placental inflammation has emerged [1], [4], [25], [26], [27], [28], [29]. Central relationship between the periodontal disease and preterm birth (PTB) is due to an inflammatory response system responding to signal from bacterial invasion [30], [31].…”
Section: Periodontal Disease and Oral Microbiomementioning
confidence: 99%
“…Specifically, it has been investigated the role of the Gram-negative periodontal pathogen FN, an opportunistic pathogen agent having a specific role in the pathogenesis of different periodontal conditions, and it is increasingly recognized as an important agent of PTB [42], [50]. FN is credited with the distinction of being the most crucial pathogen implicated in the pathogenesis of periodontitis [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], counting its systemic effects on immune system [59], [60]. The localized infection and inflammation of the mouse placenta mediated by oral FN colonization have been described previously by several researchers who suggested that the hematogenous transmission of this bacterium had a detrimental effect on pregnancy, producing intrauterine inflammatory response [51].…”
Section: The Linkage Between Fn and Ptbmentioning
confidence: 99%
See 2 more Smart Citations